2022
DOI: 10.1186/s12888-022-04474-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between attitudes toward COVID-19 infection, depression and anxiety: a cross-sectional survey in Japan

Abstract: Background Although negative attitudes are known to develop with experiences of COVID-19 infection, it remains unclear whether such attitudes contribute to depression and anxiety as sequelae of COVID-19. We aimed to investigate the relationships between attitude towards COVID-19 infection and post-COVID-19 depression and anxiety. Methods A cross-sectional survey of COVID-19 recovered patients was conducted from July to September 2021 in Japan. Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
0
7
0
4
Order By: Relevance
“…Inaddition to the mental health problems observed before the post-acute phase[15,18–20,22,23,66], psychological distress after PASC becomes apparent may lead to prolonged PASC. COVID-19 survivors often face discrimination, negative thoughts about COVID-19, and experience unemployment after recovery, which can exacerbate mental health problems [28,29][67][68]. These factors may, in turn, lead to prolonged PASC due to resultant mental health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inaddition to the mental health problems observed before the post-acute phase[15,18–20,22,23,66], psychological distress after PASC becomes apparent may lead to prolonged PASC. COVID-19 survivors often face discrimination, negative thoughts about COVID-19, and experience unemployment after recovery, which can exacerbate mental health problems [28,29][67][68]. These factors may, in turn, lead to prolonged PASC due to resultant mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who recover from COVID-19 are at risk of developing new mental health problems[4,2427]. COVID-19-related experiences, such as perceived discrimination and negative thoughts about the infection, were reported to be associated with mental health problems, independent of pre-existing mental health problems[28,29]. Several cross-sectional studies also suggest that preceding PASC affects mental health after recovery[30–34], and longitudinal studies have suggested that presence of PASC predicts mental health problems[35,36].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the association between exercise participation and Internet Addiction (IA), we conducted Modified Poisson regression analysis ( 20 , 21 ). This analysis allowed us to examine the relative risk (RR) and 95% confidence interval (CI) of the dependent variable (DV) in relation to the independent variables (IV) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the experiences of participants and families being maligned were defined as those who answered “yes” to the question “Have you or your family ever been maligned by someone as a result of your infection status?”. The variables associated with both outcome variables and exposure variables were used as covariates: sex (male, female, others) 11 , 32 , age group (20–29, 30–39, 40–49, 50–59, 60–69, 70–79, 80–89, ≥ 90) 11 , 33 35 , level of education (junior high school, high school, vocational school or junior college, university, and postgraduate school) 11 , 36 , 37 , job status (employed and unemployed) 33 , 36 , 38 , Cohabitant status (living alone and living together) 11 , 35 , duration after infection 5 , 39 , hospitalization status at infection (hospitalized and not hospitalized) 3 , 40 . Sex was later converted to the binary variable by merging females and others.…”
Section: Methodsmentioning
confidence: 99%